Evaluation of a General Circulation Model by the CERES Flux‐by‐Cloud Type Simulator. Issue 20 (19th October 2017) - Eitzen, Zachary A.; Su, Wenying; Xu, Kuan‐Man; Loeb, Norman; Sun, Moguo; Doelling, David; Rose, Fred; Bodas‐Salcedo, Alejandro
Abstract: In this work, we use the Clouds and the Earth's Radiant Energy System (CERES) FluxByCloudTyp data product (FBCTObs), which calculates top‐of‐atmosphere (TOA) shortwave and longwave fluxes for cloud types defined by cloud optical depth ( τ ) and cloud top pressure ( p c ), and the CERES Flux‐by‐cloud type simulator (FBCTSim) to evaluate the HadGEM2‐A model. FBCTSim is composed of a cloud generator that produces subcolumns with profiles of binary cloud fraction, a cloud property simulator that determines the cloud type ( τ, p c ) for each subcolumn, and a radiative transfer model that calculates TOA fluxes. The identification of duplicate subcolumns greatly reduces the number of radiative transfer calculations required. In the southern Great Plains region in January, February, and December 2008, FBCTSim shows that HadGEM2‐A cloud tops are higher in altitude than in FBCTObs but also have higher values of outgoing longwave radiation (OLR) than in FBCTObs, leading to a compensating error that results in an average value of OLR that is close to observed. When FBCTSim is applied to the southeast Pacific stratocumulus region in JJA 2008, the cloud tops are primarily low in altitude; however, the clouds tend to be less numerous and have higher optical depths than are observed. In addition, the HadGEM2‐A albedo is higher than that of FBCTObs for those cloud types that occur most frequently. FBCTSim is also applied to the entire 60°N to 60°S region, and it is found that there are both fewer clouds and higher albedos than observed for most cloud types, which represents a compensating error in terms of the shortwave radiative budget. Key Points: This paper introduces the CERES FluxByCloudTyp data product, which assigns TOA fluxes to cloud types that are defined by τ and p c The CERES Flux‐by‐cloud type simulator is introduced and is used to compare subgrid‐scale GCM fluxes to observed fluxes by cloud type The GCM produces fewer clouds and higher albedos than observed for most cloud types, representing a compensating error in the shortwave